On the Ecology and Silviculture of Dendrocalamus Strictus in the Bamboo Forests of Bhadravati Division, Mysore State, and Comparative Notes on the Species Bambusa, Arundinacea Ochladra Travancorica, Oxytenanthera Monostigma and O. Stocksii - Kadambi, K. (Indian Forester, 1949)
No abstract